Synthesis and Characterization of Derivatives Based on 4, - Dimercaptobiphenyl - Baghdad Science Journal (مجلة بغداد للعلوم)
Starting from 4, - Dimercaptobiphenyl, a variety of phenolic Schiff bases (methylolic, etheric, epoxy) derivatives have been synthesized. All proposed structure were supported by FTIR, 1H-NMR, 13C-NMR Elemental analysis all analysis were performed in center of consultation in Jordan Universty.